Antiulcerogenic Compounds Isolated from Medicinal Plants - Beserra, Fernando Pereira [UNESP]; Rozza, Ariane Leite [UNESP]; Vieira, Ana Júlia [UNESP]; Sérgio Gushiken, Lucas Fernando [UNESP]; Pellizzon, Cláudia Helena [UNESP] (Elsevier, 2016)
The gastric mucosa is continuously exposed to damaging agents that are involved in the pathogenesis of gastric ulcers, the most common chronic gastrointestinal disease. Common habits such as stress, coffee ingestion, tobacco, alcohol, and nonsteroidal antiinflammatory drugs' consumption contribute to the physiopathology of gastric ulcers. There is an ongoing search to discover novel bioactive gastroprotective and ulcer-healing compounds derived from medicinal plants. Among antiulcer studies using natural products, those focused on isolated compounds have brought promising results, which is important for developing new drugs against gastric ulcers. In this manuscript, we review the published antiulcer studies dedicated to isolated compounds, highlighting the chemical structure and mechanisms of action of each compound and trying to elucidate a structure-activity relationship for the tested compounds.
Keywords: alkaloids; gastric ulcer; isolated compounds; phenolic compounds; saponins; terpenes